SUSTAINABLE BUSINESS MODELS IN EMERGING MARKETS: INNOVATIONS AND CHALLENGES FOR ENTREPRENEURS (Web of Teachers: Inderscience Research, 2025)
Sustainable business models are becoming more and more relevant in emerging markets. Rapid economic growth, environmental and social issues, and the emergence of new technologies in these markets create significant opportunities and challenges for entrepreneurs. Below are innovations related to sustainable business models in emerging markets and what they are facing. In this article, we will focus on these topics separately.